Assessing knowledge and awareness of multiple sclerosis among adults attending Hospital Pakar Universiti Sains Malaysia (HPUSM) outpatient clinics - Saidi, Nur Fatini Idrus (Universiti Sains Malaysia, 2025)
Multiple sclerosis (MS) is a chronic, idiopathic autoimmune disease characterized by inflammation of the central nervous system, leading to demyelination and subsequent axonal degeneration, and typically affecting young adults (Calabresi, 2004). This study aimed to assess the level of knowledge and awareness of MS among adults attending the outpatient clinic at Hospital Pakar Universiti Sains Malaysia (HPUSM) and to determine whether there is any association between knowledge or awareness and selected socio-demographic factors. A cross-sectional study was conducted among 147 adult participants at HPUSM outpatient clinic using a validated self-administered questionnaire, the MS Knowledge Questionnaire (MSKQ-25) and awareness questionnaire. Data were analyzed using descriptive statistics and Chi-square tests to identify associations between knowledge and awareness levels and socio-demographic variables. The mean knowledge score was 7.88 ± 4.626 with 84.4% of participants demonstrating poor knowledge. The mean awareness score was 2.90 ± 1.98, and only 22.4% of participants had high awareness. There was a statistically significant association between source of information and awareness level (p = 0.018). However, no significant associations were found between knowledge and age (p = 0.363), gender (p = 0.076), or educational level (p = 0.119). In conclusion, the findings indicate a generally low level of knowledge and awareness about MS among the studied population